2021
DOI: 10.1097/mcg.0000000000001604
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Pediatric Gastroesophageal Reflux Disease

Abstract: Gastroesophageal reflux (GOR) is defined as "the passage of gastric contents into the esophagus with or without regurgitation and vomiting" and gastroesophageal reflux disease (GORD) is defined "when GOR leads to troublesome symptoms affecting the daily functioning and/or complications." This definition was first developed in 2006 by the Montreal consensus group (1) and later on adopted by pediatric gastroenterology societies such as ESPGHAN and NASPGHAN in 2009 (2). The definition of gastroesophageal reflux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 241 publications
0
3
0
Order By: Relevance
“…Infant regurgitation is one of the most frequent DGBIs in children with a prevalence of about 20% ( 2 , 8 , 32 , 33 ). Gastroesophageal reflux (GER) is a normal physiologic event that occurs multiple times a day and manifests itself as infant regurgitation ( 8 , 34 ).…”
Section: Infant Regurgitationmentioning
confidence: 99%
“…Infant regurgitation is one of the most frequent DGBIs in children with a prevalence of about 20% ( 2 , 8 , 32 , 33 ). Gastroesophageal reflux (GER) is a normal physiologic event that occurs multiple times a day and manifests itself as infant regurgitation ( 8 , 34 ).…”
Section: Infant Regurgitationmentioning
confidence: 99%
“…5,7,31 Several different underlying mechanisms have been suggested to explain the discrepancy in non-erosive GERD phenotype prevalence between children and adults. 32 Mahoney et al 15,28 hypothesized a predominance of peripheral and central sensitization in children. 33,34 In an adult study, patient with FH have shown a significantly higher balloon distention mechano-sensitivity and acid perfusion chemosensitivity, when compared to either patients with NERD or healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal hypervigilance, a form of hyperawareness and early detection of painful esophageal stimuli, is independently and significantly associated with symptoms severity and is consistent across reflux groups. 32 Nonetheless, in patients with FH, visceral neural pathways dysfunction and/or cortical processing alterations may also contribute and mediate esophageal hypersensitivity. 44 Interestingly, evoked cortical responses are produced by mucosal acid exposure in FH subjects prior to inducing heartburn.…”
Section: Discussionmentioning
confidence: 99%